158k views
2 votes
The function c(f) = 5/9 (f-32) allows you to convert degrees to Fahrenheit to degrees Celsius. Find the inverse of the function so that you can convert degrees Celsius back to degrees Fahrenheit

User Vijay Gill
by
5.5k points

2 Answers

6 votes

For this case we have the following function:


c (f) = \frac {5} {9} (f-32)

We must find the inverse function. For this we follow the steps below:

Replace c (f) with y:


y = \frac {5} {9} (f-32)

We exchange variables:


\frac {5} {9} (y-32) = ff = \frac {5} {9} (y-32)

We solve for "y":


\frac {5} {9} (y-32) = f

We multiply by
\frac {9} {5}on both sides of the equation:


y-32 = \frac {9} {5} f

We add 32 to both sides of the equation:


y = \frac {9} {5} f + 32

We change y by
c^( -1) (f):


c^(-1) (f) = \frac {9} {5} f + 32

Answer:


c^(-1) (f) = \frac {9} {5} f + 32

User Andrew Marsh
by
5.7k points
4 votes

Answer:


f(c)=(9)/(5)c+32

Explanation:

Given function that is used to convert degrees to Fahrenheit to degrees Celsius,


c(f)=(5)/(9)(f-32)

Let y represents the output value of the function and x represents the input value,


y=(5)/(9)(x-32)

Switch x and y,


x=(5)/(9)(y-32)

Isolate y,


9x=5(y-32)


(9)/(5)x=y-32


\implies y = (9)/(5)x+32


\implies f(c)=(9)/(5)c+32

Which is the required function.

User Darkbluesun
by
7.1k points